2022
DOI: 10.1093/eurheartj/ehac286
|View full text |Cite
|
Sign up to set email alerts
|

Functional stress imaging to predict abnormal coronary fractional flow reserve: the PACIFIC 2 study

Abstract: Aims The diagnostic performance of non-invasive imaging in patients with prior coronary artery disease (CAD) has not been tested in prospective head-to-head comparative studies. The aim of this study was to compare the diagnostic performance of qualitative single-photon emission computed tomography (SPECT), quantitative positron emission tomography (PET), and qualitative magnetic resonance imaging (MRI) in patients with a prior myocardial infarction (MI) or percutaneous coronary intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Direct comparison of ischaemia testing is scarce. The prospective head to head comparison of coronary CT angiography, myocardial perfusion SPECT, PET and hybrid imaging for diagnosis of ischemic heart disease using fractional flow reserve as index for functional severity of functional stenosis-2 (PACIFIC-2) study 9 investigated the diagnostic performance of qualitative 99mTc-tetrofosmin single-photon emission CT (SPECT) vs. quantitative [15O]H2O positron emission tomography (PET) vs. qualitative CMR in patients with a prior myocardial infarction or percutaneous coronary intervention (PCI). When using as reference fractional flow reserve (FFR) ≤ 0.80, SPECT had a sensitivity 67%, specificity 65% vs. PET sensitivity 81%, specificity 65%.…”
Section: Nuclear Cardiologymentioning
confidence: 99%
“…Direct comparison of ischaemia testing is scarce. The prospective head to head comparison of coronary CT angiography, myocardial perfusion SPECT, PET and hybrid imaging for diagnosis of ischemic heart disease using fractional flow reserve as index for functional severity of functional stenosis-2 (PACIFIC-2) study 9 investigated the diagnostic performance of qualitative 99mTc-tetrofosmin single-photon emission CT (SPECT) vs. quantitative [15O]H2O positron emission tomography (PET) vs. qualitative CMR in patients with a prior myocardial infarction or percutaneous coronary intervention (PCI). When using as reference fractional flow reserve (FFR) ≤ 0.80, SPECT had a sensitivity 67%, specificity 65% vs. PET sensitivity 81%, specificity 65%.…”
Section: Nuclear Cardiologymentioning
confidence: 99%
“…[ 6 , 7 ] PET also has better temporal resolution as it can register events faster than SPECT, and the gantry in PET is stationary, compared to that in SPECT which is rotational. Temporal resolution is also closely related to the sensitivity of the imaging system, which confers PET an advantage [ 8 , 9 ].…”
Section: Advantages Of Cardiac Pet Vs Spectmentioning
confidence: 99%
“…A study by Desiderio et al in 2018 found that the average PET myocardial perfusion imaging (MPI) radiation exposure was 3.7 (3.2–4.1) mSv per study, as opposed to the average SPECT MPI radiation exposure which was 12.8 (12.2–14.3) mSv [ 8 ]. This is reduced even further as newer digital PET cameras allow for usage of lower doses of radiotracers (routine Sub-milliSievert PET scans can be performed among patients with BMI < 30 kg/m 2 ) [ 9 ].…”
Section: Advantages Of Cardiac Pet Vs Spectmentioning
confidence: 99%
“…
Performance of positron emission tomography (PET), magnetic resonance imaging (MRI), and single-photon emission computed tomography (SPECT) for diagnosing fractional flow reserve (FFR)-defined significant coronary artery disease (CAD) on a per-patient level. A 67-year-old male who underwent multiple diagnostic tests because of stable angina serves as a graphical summary of the PACIFIC 2 study (Driessen et al 3 ). The final diagnosis is made using invasive catheter coronary angiography that showed a significant stenosis of the mid-portion of the left descending artery (left panel, arrowhead).
…”
mentioning
confidence: 99%
“…Reported in this issue of the European Heart Journal, PACIFIC 2 is a prospective, single-centre study that compared the diagnostic performance of quantitative stress PET with [ 15 O]water and both qualitative stress-rest cardiac MRI and 99m Tc-tetrofosmin SPECT in patients with established coronary artery disease (CAD), using invasive FFR as the standard of reference. 3 Ninety percent of the cohort had a prior percutaneous coronary intervention (PCI), while 53% had a prior myocardial infarction (MI). PET had the highest sensitivity (81% vs. SPECT 67% and MRI 66%) for diagnosing haemodynamically significant (FFR ≤0.80) CAD, while the specificities for all three imaging modalities were similar.…”
mentioning
confidence: 99%